Elevated glucose concentrations promote receptor-independent activation of adherent human neutrophils: an experimental and computational approach - Kummer, Ursula (Biophysical journal, 2007)
Neutrophil activation plays integral roles in host tissue damage and resistance to infectious diseases. As glucose uptake and NADPH availability are required for reactive oxygen metabolite production by neutrophils, we tested the hypothesis that pathological glucose levels (≥12 mM) are sufficient to activate metabolism and reactive oxygen metabolite production in normal adherent neutrophils. We demonstrate that elevated glucose concentrations increase the neutrophil’s metabolic oscillation frequency and hexose monophosphate shunt activity. In parallel, substantially increased rates of NO and superoxide formation were observed. However, these changes were not observed for sorbitol, a nonmetabolizable carbohydrate. Glucose transport appears to be important in this process as phloretin interferes with the glucose-specific receptor-independent activation of neutrophils. However, LY83583, an activator of glucose flux, promoted these changes at 1 mM glucose. The data suggest that at pathophysiologic concentrations, glucose uptake by mass action is sufficient to activate neutrophils, thus circumventing the normal receptor transduction mechanism. To enable us to mechanistically understand these dynamic metabolic changes, mathematical simulations were performed. A model for glycolysis in neutrophils was created. The results indicated that the frequency change in NAD(P)H oscillations can result from the activation of the hexose monophosphate shunt, which competes with glycolysis for glucose-6-phosphate. Experimental confirmation of these simulations was performed by measuring the effect of glucose concentrations on flavoprotein autofluorescence, an indicator of the rate of mitochondrial electron transport. Moreover, after prolonged exposure to elevated glucose levels, neutrophils return to a “nonactivated” phenotype and are refractile to immunologic stimulation. Our findings suggest that pathologic glucose levels promote the transient activation of neutrophils followed by the suppression of cell activity, which may contribute to nonspecific tissue damage and increased susceptibility to infections, respectively.